CLINICAL FEATURES AND TREATMENT MODALITIES OF THE GUILLAIN-BARRE SYNDROME A CASE REPORT - Dalipi, Teuta; Sulejmani, Haris; Zafirova, Ivana; Bogdanovski, Nenad (Journal of Morphological Sciences, 2024)
Guillain Barré syndrome refers to an inflammatory disorder that affects numerous spinal nerve roots (most commonly the anterior ones), often in conjunction with proximal segments of peripheral nerves. Guillain-Barré syndrome (GBS) and its variations are classified as immune-mediated post-infectious neurological conditions. The yearly incidence ranges between 0.5 and 2 cases per 100,000 people. It usually appears in the spring or fall.The clinical examination results and history may strongly imply GBS. A lumbar puncture (LP) is commonly performed to look for albuminocytologic dissociation. However, this result should not be used to make a diagnosis of GBS; cerebrospinal fluid (CSF) protein levels are still normal in a considerable proportion of patients during the first week of symptoms, particularly in individuals with a Miller-Fisher variation.We represent a case of A 65-year-old patient who was transported to the UC via ambulance due to bilateral limb weakness.First hospitalization was at university clinic for Neurology Skopje with symptomatology since 3 months ago. The patient tested positive for COVID-19,and his condition cleared up with just minor symptoms. After two weeks, the patient developed weakness in both legs and was unable to get out of bed. The patient eventually lost the ability to move all four limbs and experienced full loss of sensation in them. According to the findings of the International Guillain-Barré Syndrome Outcome Study, there are regional differences in Guillain-Barré syndrome, including a lack of access to immunotherapy in low-income countries. There is a need to increase access to therapy for all Guillain-Barré syndrome patients, as well as to discover effective disease-modifying medicines that can decrease the degree of nerve destruction. Key words : Guillain-Barré syndrome,COVID-19,bilateral limb weakness,lumbar puncture.